2019
DOI: 10.3390/en12061114
|View full text |Cite
|
Sign up to set email alerts
|

Energy Analysis of 4625 Office Buildings in South Korea

Abstract: The purpose of the present study was to investigate the relevance of building thermal performance and characteristics to building energy consumption. This paper reports an energy analysis of 4625 office buildings in Seoul, South Korea, using data from the Korean national building energy database and architectural database. The following four research questions were investigated: (1) Do old buildings consume more energy than new ones? (2) Have strict prescriptive building energy codes contributed to the reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It can be found that HVAC and lighting systems, as main energy consumption systems of commercial buildings, significantly influence their energy consumption, specifically the percentage of air-conditioned floor area and the percentage usage of LED, the former influencing office and retail, and the latter influencing office. It is generally believed that new buildings consume less energy than older buildings, and it is concluded that the age of office buildings does not correlate with EUI [37] . This study found that the EUI of hotel, retail, and mixed development was significantly influenced by the year obtained TOP/CSC (reflecting the age of the building), with newer buildings showing higher energy consumption, which complements the existing studies on the influential of building age on EUI in various commercial building types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that HVAC and lighting systems, as main energy consumption systems of commercial buildings, significantly influence their energy consumption, specifically the percentage of air-conditioned floor area and the percentage usage of LED, the former influencing office and retail, and the latter influencing office. It is generally believed that new buildings consume less energy than older buildings, and it is concluded that the age of office buildings does not correlate with EUI [37] . This study found that the EUI of hotel, retail, and mixed development was significantly influenced by the year obtained TOP/CSC (reflecting the age of the building), with newer buildings showing higher energy consumption, which complements the existing studies on the influential of building age on EUI in various commercial building types.…”
Section: Resultsmentioning
confidence: 99%
“…HVAC represents 43% of electricity consumption for retail and office buildings. [37] Seoul, South Korea Year built, number of floors, number of elevators, and total floor area Coefficients of determination of statistical analysis In office buildings, new buildings did not always consume less energy than old buildings. The district, year built, number of floors, number of elevators, and total floor area do not adequately explain annual total energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the segregation method used to determine the heating and cooling energy has been widely employed ( Ahn et al., 2019 ; Robison, 1992 ; Kwag et al., 2020 ), the obtained results are still a crude estimate of the real heating and cooling energy. Future research is encouraged to employ improved estimation methods in determining heating and cooling energy use.…”
Section: Discussionmentioning
confidence: 99%
“…As such, based on Figure S2 in the Supplemental information , which shows high electricity usage during the cooling period (June – September) and similarly heightened gas usage during the heating period (October – March), electricity was considered the dominant energy source for cooling purposes while gas energy was considered the dominant energy source for heating purposes. Finally, the monthly seasonal varying energy use, which in our case equated to monthly cooling/heating energy use, was determined as the difference between monthly total electric energy consumption ( E total _ monthly )/monthly gas energy consumption G total _ monthly ) and E l / G l as shown in Equations 2 and 3 , and this approach has been employed in several previous studies ( Ahn et al., 2019 ; Li et al., 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have evaluated Seoul's building morphology (Kang et al, 2020; Yi et al, 2016), solar radiation profile (Jee et al, 2017), office building energy consumption (Ahn et al, 2019), and rooftop PV potential (Byrne et al, 2015; Hong et al, 2017). Overall, these assessments identify substantial citywide rooftop solar potential.…”
Section: Case Study Of Eunpyeong‐gu Seoul South Koreamentioning
confidence: 99%